Improvement of sulfur and water resistance with Fe-modified S–MnCoCe/Ti/Si catalyst for low-temperature selective catalytic reduction of NO with NH3. (September 2022) - Qiu, Lu; Li, Dengkui; Li, Hanliang; Ren, Zhaoyong; Zhu, Zhenye; Ouyang, Feng; Guo, Mingxin
Abstract: The low-temperature SCR of NOx by NH3 is restricted in application since the catalysts is easily poisoned by sulfur and water. The Fe modified Mn–Co–Ce/TiO2 /SiO2 catalysts synthesized via impregnation method and sulfating were evaluated for low-temperature NH3 -SCR in the presence of SO2 and H2 O. The calcination temperature and loading amounts of Mn, Fe, Co and Ce were optimized. Adding of Fe into S–MnCoCe/Ti/Si played an important role in resistance to sulfur and water poisoning. The optimal calcination temperature was 380 °C and the optical mass loading of the catalyst was 10% of Mn, 10% of Fe, 1% of Co and 4% of Ce. The optimal S–MnFeCoCe/Ti/Si catalyst maintained high NOx conversion of 93% at reaction temperature of 160 °C in the presence of 50 ppm SO2 and 10 vol% H2 O. The catalytic activity did not continue to fall after two times of repeated used in the temperature range of 100–200 °C, indicating its excellent sulfur and water durability and stability in the presence of SO2 and H2 O. The interaction between MnOx and FeOx enhanced sulfur and water durability rather than other bi-metal interactions. Furthermore, the mechanism of Fe improving resistance to SO2 and H2 O was discussed. Graphical abstract: Image 1 Highlights: Excellent SO2 and H2 O resistance was achieved by Fe doping. The optical mass loading was 10% of Mn, 10% of Fe, 1% of Co and 4% of Ce. The optimal catalyst maintained 93% NOx conversion at 160 °C under SO2 and H2 O. Significance of Mn–Fe interaction was higher than other bi-metallic interactions. Electron transfer from Fe 2+ to Mn 4+ restrains the electron transfer from SO2 to Mn 4+ .